2020
DOI: 10.1177/1556984520949955
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Reoperative Mitral Valve Surgery: Technical Considerations and Clinical Outcomes

Abstract: As patients with cardiac disease live longer, reoperative mitral valve surgery has become more common. Although these operations are technically challenging and of high risk, outcomes continue to improve. Minimally invasive techniques, better cardioprotective strategies, and advanced perioperative care have contributed to this. In this review, we discuss surgical approaches, intraoperative strategies, novel catheter-directed devices, and clinical outcomes of contemporary reoperative mitral valve surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 113 publications
(166 reference statements)
1
4
0
Order By: Relevance
“…The mean ICU and hospital stay duration in our series were 68.75±76.06 hours and 10.79±6.79 days, respectively. These findings are constant with other studies in the literature, showed a mean hospital stay ranges from 6.2 to 17.2 days and ICU stay from 18 hours to 13.5 days [7]. In the current era of less-invasive techniques, the right mini-thoracotomy is an attractive alternative to median sternotomy for mitral reoperations to reduce hospital and ICU stay duration and minimize morbidity and mortality.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The mean ICU and hospital stay duration in our series were 68.75±76.06 hours and 10.79±6.79 days, respectively. These findings are constant with other studies in the literature, showed a mean hospital stay ranges from 6.2 to 17.2 days and ICU stay from 18 hours to 13.5 days [7]. In the current era of less-invasive techniques, the right mini-thoracotomy is an attractive alternative to median sternotomy for mitral reoperations to reduce hospital and ICU stay duration and minimize morbidity and mortality.…”
Section: Discussionsupporting
confidence: 85%
“…However, scant data exists in the literature regarding the specific outcome evaluation after redo-mitral valve replacement in this group of patients. In the contemporary literature, reoperative mitral valve surgery remains a surgical challenge due to higher preoperative risk factors that lead to higher rates of in-hospital mortality and postoperative complications [5,7].…”
Section: Discussionmentioning
confidence: 99%
“…Ann Transl Med 2021 | http://dx.doi.org/10.21037/atm-21-2407 via minimally invasive approaches and resternotomy range from 0% to 13% and from 4.2% to 12%, respectively (17).…”
Section: Discussionmentioning
confidence: 99%
“…Although evidence is currently limited to case series, this relatively low procedural risk intervention has successfully been used to restore haemodynamic stability in post-MI patients with a mechanical complication [49,50]. Other studies have demonstrated the successful application of transcatheter mitral valve repair for the correction of ischemic mitral valve regurgitation in those with advanced chronic mitral valve regurgitation in stable condition and in acute, unstable patients who are not surgical candidates [51]. The use of percutaneous technologies has the potential advantages of rapidly decreasing left ventricular, atrial, and pulmonary artery pressures and increasing cardiac output after mitral valve regurgitation correction.…”
Section: Percutaneous Ventricular Septal Rupture Closure and Edge-to-...mentioning
confidence: 99%